Modernising the EU’s public procurement regime: a blueprint for real simplicity and flexibility - Arrowsmith, Sue (Sweet and Maxwell, 2012)
On 20 December 2011 the European Commission published its proposals for two new procedural directives on public procurement, one to replace Public Sector Directive 2004/18 and one to replace Utilities Directive 2004/17, with the stated aims of “simplification” and “flexibilisation” (sic) of the rules to improve value for money. However, following the pattern of the previous reforms in 2004, whilst the proposals do indeed provide for some additional flexibility, they have at the same time in many respects introduced more rigidity and burdensome requirements for Member States. Furthermore, these and other changes proposed will result in a set of rules which is vastly more complex than the current regime that the proposals purport to simplify.